Hadis Kepemimpinan Perempuan: Penerapan Metode Qira’ah Mubadalah - Yumidiana Tya Nugraheni; Euis Nur Fu'adah (Matan : Journal of Islam and Muslim Society, 2020)
Islam is a complete and perfect religion that gives mercy from the texts in the Qur'an and the Hadith. Grace in Islam applies to men and women. Islam carries a message that elevates the degree of women to be equal to men in society. There are verses of the Qur’an and also the hadith that explain the position of women and men. This research aims to determine the study of the traditions and attitudes of women leadership traditions and the application of the Qiro'ah mubadalah method to women's leadership. This research includes library research with Qiroah Mubadalah method. Research results include; the hadiths on women's leadership are included in the category of authentic hadith based on the study of sanad and matan and the hadiths of female leadership relate to certain socio-political contexts. Women's leadership traditions include casuistic hadiths. Women in the context of the hadith do not have the capacity to be leaders. Women who have the capacity of leaders are women who have a responsible attitude, serve, provide kindness, and prosper the community. Then women can be made leaders. The moral idea of the hadith is responsibility as a leader.